2017
DOI: 10.1007/s00701-017-3295-9
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged hypotension after carotid artery stenting: incidence, predictors and consequences

Abstract: PH was more prevalent in patients with contralateral high-degree carotid stenosis and patients without diabetes mellitus after CAS. PH did not cause any post-procedural complications or major vascular events at follow-up, but it resulted longer hospital stays. Further studies are needed to better define the pathophysiologic mechanisms underlying these hemodynamic alterations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…A total of 1430 literature records were retrieved, including 435 records in Chinese and 995 records in English. Finally, 17 3 5,7,10 –12,17 –26 studies were finally included in the meta-analysis. The flow of the literature screening process is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 1430 literature records were retrieved, including 435 records in Chinese and 995 records in English. Finally, 17 3 5,7,10 –12,17 –26 studies were finally included in the meta-analysis. The flow of the literature screening process is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…The 17 3 5,7,10 –12,17 –26 studies included 7 3,7,11,17 –20 case-control studies and 10 4,5,10,12,21 –26 cross-sectional studies. In addition, the sample contained a total sample size of 2843 cases, as well as 897 patients with postoperative hypotension and 14 patients with exposure factors (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several physicians demonstrated this phenomenon through an intraluminal rub test and observed that patients with contralateral stenosis were more likely to have a significant hypotensive response. 18 It has been hypothesized that the carotid sinus may have physiologic baroreceptor reserve, 19 which is impaired in bilateral carotid artery stenosis. This may explain why patients with contralateral stenosis are more susceptible to PHD during or after CAS.…”
Section: The Risk Factors For Phdmentioning
confidence: 99%
“…The incidence of this vasodepressor reaction ranges between 5 and 76%, whereas the incidence of persistent hypotension ranges between 11 and 35%. [ 3 4 5 6 7 8 9 ] Variation in incidence across the studies can be largely explained because of the differences in definition, inclusion criteria and procedural technique. In a meta-analysis of 27 randomised trials with over 4000 patients, the pooled estimate for hypotension was 12.1%, 19.2% for persistent hypotension, 12.2% for bradycardia, and 12.5% for both hypotension and bradycardia.…”
Section: Efinition Of Hdmentioning
confidence: 99%